Teachers' and Student's Perception on Shadow Education in Mathematics Learning - Acharya, Megh Raj (Butwal Campus Journal, 2024)
The title of this study was Teachers and Students Perceptions of Shadow Education in Mathematics learning. This study aims to cover the perceptions of teachers and students regarding shadow education. A qualitative research design specifically using narrative interviews, was employed in this study. The main tools of this study were interview and focus group discussion. The primary data source of this study were two community schools and mathematics teachers. Two students and one Teacher from each of the two schools were selected based on purposive sampling . After collecting the data themes were generated through coding. Both positive and negative perception were observed among teachers and students. A positive expectation was that coaching class would enhance students achievements while negative expectation was that regular class attendance might decrease. An improvements in teachers’ economics situations was a positive aspects. Shadow education was also seen to increase students self confidence and enhance use of materials when solving mathematical problem, which were considered beneficial aspects.